Quiet places [videorecording] a look at ecotourism in the Philippines - Gamboa, Joonee ([Quezon City] Bookmark Video)
The Philippines is a land of great natural reality. Through the years, many attemps have been made to take advantage of this and develop tourism into one of the country's biggest revenue- earners. With the continuing destruction of the environment and the rapid loss of the very respurces that are being counted upon to draw visitors, it has become necessary to examine what is being done, and determine how the national tourism development program may be revised.
Quiet Places: a look at ecotourism in the Philippines is about a new, more relevant and more gentle kind of tourism. A way of travelling that has become popular all over the world and is finally gaining advocacy oin the Philippines.
Learn more about the concepts behind ecotourism; witness examples of how they are implemented in the Philippines. and see why they are now regarded as the appropriate and sustainable alternative to the more damaging and strenuous commercialism that prevails in the mainstream tourism sector today.
Find your way to extraordinary places on the archipelago where ecotourism in the marine and riverine settings is being promoted, with remarkable results. Places such as the Tubbhataha reefs in the Sulu Sea; Anilao in Batangas; Bais in Negros Oriental; The Lobo9c and Abatan Rivers in Bohol; The Agusan Marsh in Mindanao; Donsol in Sorsogon; The Batanes Islands; Lake Sebu in South Cotabato; Honda Bay and Coron in Palawan and Turle Island in Tawitawi. Meet some people who are playing important roles in the promotion of the new trusts for an industry dedicated more and more to conserving nature's gifts, while paving the way for economic.
Keywords: Ecotourism -- Philippines